Socio-economic Conditions and Welfare Levels of Lobster Fishers in Tabanan Regency, Bali - Mochammad Rhasaan Habibie; I Ketut Wija Negara; Gede Surya Indrawan (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
Lobster (Panulirus spp.) is a high-value commodity, making it a target for small-scale fishers in Tabanan Regency, Bali. Most of the poverty in Tabanan Regency is concentrated in coastal villages, where most residents work as fishers. This study aims to determine the socio-economic conditions and welfare levels of lobster fishers in Tabanan Regency, Bali measured in 10 welfare indicators according to the Central Bureau of Statistics (BPS) including income, proportion of expenditure, education, health, quality of housing, housing facilities, ownership status of housing, ownership of Information and Communication Technology (ICT) tools, ease of obtaining public facilities, and social access. This research is descriptive, quantitative, and qualitative, using questionnaire-based data collection techniques, and was conducted with 89 lobster fishers in August 2024 in Tabanan Regency, Bali. All respondents answered the same questions using a value scale of 1 to 3. The score values were totaled and averaged to produce three categories: prosperous, moderate, and not prosperous. This study shows that the socioeconomic conditions of lobster fishers in Tabanan Regency are generally good. Among 89 respondents in Tabanan Regency, Bali, 93% are in the 2.42-3.12 range, indicating the prosperous category, and the remaining 7% are in the 1.71-2.41 range, indicating the moderate category. There are no fishers classified as not prosperous.